INFORMATION SOURCES OF TRADING DECISION MAKING AS DETERMINING FACTORS FOR COGNITIVE BIASES - Heboyan, Arevik (Modern Psychology, 2023)
In the article the issues of trading decision making are being discussed in the lights of cognitive biases in uncertainty. The process of trading stocks requires buy/sell decision making in uncertain conditions under extreme time constraints. In ever-changing market decisions are made momentarily and cognitive biases and heuristics determine the speed and quality of decisions. Information and expectations are the core of cognitive component of the process and can influence biases.